KEEFEKTIFAN MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP KETERAMPILAN MENULIS TEKS NEGOSIASI SISWA KELAS X SMA NEGERI 3 MAROS KABUPATEN MAROS - ELVI RAHMI (Jurnal Muara Pendidikan, 2018)
This research aimed to find out the effectiveness of using problem based learning model toward students’ ability in writing negotiation text student of class X SMA Negeri 3 Maros. This research applied an experimental which involved one class. The population of this research was the students of class X of SMA Negeri 3 Maros consist of 361 students from ten classes. The sample of this research was students of X IPA 4 consist of 35 students. The sampling was selected by used simple random sampling technique. The instrument was the instrument which related with the learning proses in writing negotiation text using problem based learning model and writing negotiation text test. The test was used in the beginning (pretest) and in the end (posttest). The data analysis used descriptive statistic and inferential statistic. The result of descriptive statistic indicated the effectiveness of problem based learning in students’ ability in writing negotiation text of the students of X IPA 4 SMA Negeri 3 Maros. That was proven by the student’ test score using the problem based learning was in average category with score average in 78.9. The inferential statistic result was the calculation of significance test value ttest> ttable, was 4,268 > 1,690. That indicated that the alternative hypothesis was accepted which means that the problem based learning model was effective in students’ ability in writing negotiation text of the student in class X IPA 4 SMA Negeri 3 Maros. Based on the data analysis and the finding, that concluded that problem based learning model was effective in students’ ability in writing negotiation text of students of class IPA 4 SMA Negeri 3 Maros, Maros regency. Based on that conclusion, some suggestions were interpose related to this research. For the Bahasa and Sastra Indonesia teacher, especially for teacher class X IPA 4 SMA Negeri 3 Maros have to enrich their teaching model in writing negotiation text and always give training to the students in writing text and for the students they have to accustom to write negotiation text to make them easy and make variations of their work.